STUDI KONSERVASI SUMBERDAYA ALAM HAYATI PADA MASYARAKAT TENGGER DI RESORT RANU PANI, TAMAN NASIONAL BROMO TENGGER SEMERU - Meyliana Astriyantika; Harnios Arief; Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
Ranu Pani village is an enclave village located in a area Ranu Pani Resort, Bromo Tengger Semeru National Park. Purpose of this study was to access the understanding and motivation of Tengger society, the level of economic dependency, and examines the real action of conservation. Methods in use begins with a literature study, field observation, and questionnaires. The trust believed that the forest is the system of life that must be preserved for the sake of happiness the offspring, forming positiveness on Tengger society to maintain the forest in order to preservein an hereditary manner, utilization done very limited only adoption of kindling the trees that is dead and retrieval grass for cattle course. The economic society derived from the results of the field so as not to be depended from biological resources in the forest. Ranu Pani village society sometimes actively in conservation activities through planting, forest ares extinguish the blaze, and joined in the conservation cadre society ang public patner of rangers. Various counseling who regularly performed by the management of Ranu Pani Resort, capable of being creates understanding conservation for Ranu Pani society so take care of security of the area an understand the established rules. Keywords: conservation, enclave villlage, Tengger society, Ranu Pani Resort, Bromo Tengger Semeru National Park.